PENGARUH IKLIM KERJA SEKOLAH TERHADAP KINERJA GURU - Khomarunizar; Abdul Adib; Abdul Adib; Achmad Sarbanun (UNISAN JURNAL, 2022)
The purpose of this study was (1) to determine whether there is an influence of madrasa principal leadership on teacher performance, (2) to find out whether there is an effect of madrasa climate on teacher performance, (3) to determine whether there is an influence of madrasa principal leadership and madrasa climate simultaneously on teacher performance. teacher performance. The research was conducted using multiple linear regression analysis and quantitative methods. . The population in this study amounted to 30 teachers, the samples taken were 19 teachers at MTs Nurush Shomad and 11 teachers at MTs Islamiyah. Data collection techniques used in this study consisted of questionnaires, documentation, analytical techniques. Using multiple linear regression analysis techniques, to find the influence between the variables of madrasah leadership (X1), madrasa climate (X2) and teacher performance (Y). The results of the study are as follows: (1) There is an influence of madrasah leadership on teacher performance in MTs Nurul Falah with a percentage of 56.7%, There is an influence of Islamic climate on teacher performance in MTs Nurul Falah Subdistrict with a percentage of 47.9%, (3) There is an influence of madrasa principal leadership and madrasah climate on teacher performance at MTs Nurul Falah with a percentage of 77.3%.